Electronic band structure of zinc blende CdSe and rock salt PbSe semiconductors with silicene-type honeycomb geometry. (30th June 2015) - Delerue, Christophe; Vanmaekelbergh, D
Abstract: We report on the electronic band structure of 2D CdSe and PbSe semiconductors that have a silicene-type honeycomb geometry. Atomistic tight-binding calculations are performed on several model systems that bear a strong resemblance to the silicene-type honeycomb structures that were recently obtained by nanocrystal self-assembly. The calculated band structures are compared both to those of 2D quantum wells and graphene-type honeycomb structures. It is found that in silicene type CdSe honeycomb structures, the lowest electron conduction bands (derived from S-type nanocrystal wave functions) form a Dirac-type dispersion, very similar as in graphene. The P-type bands are usually more complex. However, when the hybridization between S- and P-type bands increases, a second Dirac cone and a genuine non-trivial flat band is observed, similar as in the case of graphene-type honeycomb structures of CdSe. There is a strong non-trivial gap between the first and second valence band, hosting the quantum spin Hall effect. Silicene-type PbSe structures show Dirac features in their bands, which however can be clouded due to the multi-valley character of PbSe.